2018
DOI: 10.11005/jbm.2018.25.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antidepressants on Mesenchymal Stem Cell Differentiation

Abstract: BackgroundUse of antidepressant medications has been linked to detrimental impacts on bone mineral density and osteoporosis; however, the cellular basis behind these observations remains poorly understood. The effect does not appear to be homogeneous across the whole class of drugs and may be linked to affinity for the serotonin transporter system. In this study, we hypothesized that antidepressants have a class- and dose-dependent effect on mesenchymal stem cell (MSC) differentiation, which may affect bone me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Previous evidence showed that both serotonin and norepinephrine affect bone metabolism and turnover, as functional serotonin and norepinephrine transporters/receptors are present in peripheral bone cells 13‒20 . Serotonin may induce proliferation of osteoblasts, whereas SSRI may inhibit bone cell function via apoptosis and impede bone mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence showed that both serotonin and norepinephrine affect bone metabolism and turnover, as functional serotonin and norepinephrine transporters/receptors are present in peripheral bone cells 13‒20 . Serotonin may induce proliferation of osteoblasts, whereas SSRI may inhibit bone cell function via apoptosis and impede bone mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, the ion channel and gap junction networks that implement bioelectric control circuits are ubiquitous, being present and function across taxa, from bacterial biofilms to mammals. [41][42][43][44][45][46][47][48][49][50][51][52] Effects on cell migration, 53 proliferation, 54 migration/pathfinding, 55,56 and stem cell differentiation 57 have been observed after modulation of neurotransmitter pathways. Even the microbiome, with many known roles in regulating mood and functioning of many organ systems, has been affected by neurotransmitter signaling.…”
Section: Possible Mechanisms: a Hypothesismentioning
confidence: 99%
“…Some studies reported that FLX may exert a role as apoptosis inducer however antiapoptotic properties of FLX also were discussed [10][11][12]. Some studies expressed that FLX could prevent cell differentiation, on the other hand, there are some documents on differentiation process improvement by FLX [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that serotonin plays a main role in cell differentiation and negatively affects bone proliferation and osteoblast differentiation. One study reported that the inhibitory effect of FLX on cell differentiation is independent of serotonin, but the other study indicated that this inhibition is related to the strong affinity of FLX to serotonin transporter system . According to the lack of clarification on FLX impact in cellular processes, more investigations are needed to elucidate the FLX properties on these cellular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation